Efficacy of radiotherapy for the treatment of cystic echinococcosis in naturally infected sheep - Rui Mao; Wen-Bao Zhang; Hong-Zhi Qi; Tao Jiang; Ge Wu; Peng-Fei Lu; Abudula Ainiwaer; Ge Shang; Lin Xu; Jie Hao; Xi Shou; Hai-Tao Li; et al. (BMC, 2017)
Abstract Background Radiotherapy is commonly used to treat cancers. To date, there has been no study focusing on the effects of radiotherapy on hydatid disease in large animals. In this study, we aim to investigate the efficiency and safety of radiotherapy for treating hydatid disease caused by Echinococcus granulosus in naturally infected sheep. Methods Ultrasound was used to screen naturally infected sheep in an echinococcosis endemic area in Xinjiang, China. A computer tomography (CT) scan confirmed the presence of hydatid cysts. Twenty sheep naturally infected with E. granulosus in the liver and/or lungs were randomly assigned into four groups receiving no irradiation, or X-ray irradiation of low (30 Gy), medium (45 Gy), and high dose (60 Gy), respectively. After three months of radiotherapy, a CT scan was performed to measure the changes in the cysts. The hepatic parasite cysts and host tissues were collected for histology and gene expression analysis. Results In the animals subject to irradiation, no significant differences were observed in their appetite, daily activities, and weight before and after radiotherapy. Severe calcification was noticed in the cysts subject to a high dose of radiation compared with the groups subject to low and medium doses. Hematoxylin and eosin staining showed that irradiation contributed to the damage of the cyst structure and nucleus in the germinal layers. Quantitative PCR demonstrated that expression of TPX and HSP70 significantly decreased in a dose-dependent manner (P < 0.05). The expression of the EPC1 decreased in the medium- and high-dose groups compared with the low-dose group (P < 0.05). Meanwhile, the expression of radiation-related apoptosis genes caspase-3 and Gadd45 decreased with an increase in the irradiation dose. Conclusions Radiotherapy is an option with satisfactory efficiency and safety for treating cystic echinococcosis in sheep with partial response or stable disease at month 3. In future, inhibition of cystic activity using radiotherapy may serve as a new regimen for treating hydatid disease.